2003
DOI: 10.1037/0022-3514.85.5.838
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Zeal and the Uncertain Self: What Makes You So Sure?

Abstract: In Studies 1-3, undergraduates with high self-esteem (HSEs) reacted to personal uncertainty-threats with compensatory conviction about unrelated issues and aspects of the self. In Study 1 HSEs reacted to salience of personal dilemmas with increased implicit conviction about self-definition. In Study 2 they reacted to the same uncertainty-threat with increased explicit conviction about social issues. In Study 3, HSEs (particularly defensive HSEs, i.e., with low implicit self-esteem; C. H. Jordan, S. J. Spencer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
192
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(208 citation statements)
references
References 83 publications
14
192
2
Order By: Relevance
“…These findings challenge the common social psychological assumption that stronger psychological needs to manage uncertainty and threat motivate individuals to show more extreme support for any ideology or social movement (whether left, right, or center) to which they subscribe or are otherwise frequently exposed (e.g., see Anson et al, 2009;Castano et al, 2011;Greenberg et al, 1986Greenberg et al, , 1990Greenberg & Jonas, 2003;Heine et al, 2006;Hogg, 2005Hogg, , 2007McGregor & Marigold, 2003;McGregor, Zanna, Holmes, & Spencer, 2001;McGregor et al, 2010;Proulx et al, 2012). Indeed, we found that the same set of epistemic, existential, and relational needs exerted opposite effects on system-justifying and system-challenging ideological outcomes (i.e., support for the Tea Party vs.…”
Section: Discussioncontrasting
confidence: 50%
“…These findings challenge the common social psychological assumption that stronger psychological needs to manage uncertainty and threat motivate individuals to show more extreme support for any ideology or social movement (whether left, right, or center) to which they subscribe or are otherwise frequently exposed (e.g., see Anson et al, 2009;Castano et al, 2011;Greenberg et al, 1986Greenberg et al, , 1990Greenberg & Jonas, 2003;Heine et al, 2006;Hogg, 2005Hogg, , 2007McGregor & Marigold, 2003;McGregor, Zanna, Holmes, & Spencer, 2001;McGregor et al, 2010;Proulx et al, 2012). Indeed, we found that the same set of epistemic, existential, and relational needs exerted opposite effects on system-justifying and system-challenging ideological outcomes (i.e., support for the Tea Party vs.…”
Section: Discussioncontrasting
confidence: 50%
“…Two recent experiments (McGregor &Marigold, 2003, andMcGregor, Nail, Marigold, &Kang, 2005) indicate that uncertainty threat can interact with unstable self-esteem to cause compensatory conviction. If self-esteem instability makes people defensive in response to uncertainty, a manipulation to increase self-integrity might work to inoculate, or at least temporarily buffer, against uncertainty threat.…”
Section: Discussionmentioning
confidence: 99%
“…Somewhat paradoxically, uncertainty in one domain of life results in an increase of certainty, reflected in extreme convictions, in other (frequently political) domains (McGregor, 2006;McGregor & Marigold, 2003). Thus, political extremism is related to a structured way of thinking aimed at making sense of society and the way it functions.…”
Section: Conspiracy Beliefs and Extreme Political Ideologymentioning
confidence: 99%